News Attention and Social-Distancing Behavior Amid COVID-19: How Media Trust and Social Norms Moderate a Mediated Relationship. Issue 6 (12th May 2022) - Jiang, Xiaoya; Hwang, Juwon; Shah, Dhavan V.; Ghosh, Shreenita; Brauer, Markus
ABSTRACT: Despite the fact that social distancing is an effective mean to slow the spread of COVID-19, individuals often fail to practice this behavior. Major US news media provided information to the public about social distancing after COVID-19 was declared a pandemic, potentially spurring this preventative health practice. Using data from a representative sample of US residents, this study aims to understand the relationship between news media attention and social-distancing behavior via three potential mediators: perceived effectiveness of social distancing, perceived susceptibility to COVID-19 infection, and perceived negative consequences of infection. Media trust and social norms concerning social distancing were included as potential moderators of these relationships, along with political ideology. With multiple regression and mediation analyses, we found that news media attention was positively associated with social-distancing behavior during this period. Perceived effectiveness of social distancing mediated this relationship, while perceived susceptibility and negative consequences of COVID-19 did not. Notably, media trust negatively moderated news attention's impact on the perceived effectiveness of social distancing, with the relationship being more pronounced among those who have lower trust in media. Political ideology did not moderate the relationship between news attention and perceived effectiveness. Further, social norms negatively moderated the relationship between perceived effectiveness and social-distancing behavior, with this relationship growing stronger among those uncertain about the adoption of social-distancing norms in their circle. Overall, the study found news media to have an important role in promoting social-distancing behavior when they emphasized safety measures across the ideological spectrum.